Temperature memory effect in shape memory polymer for over heating monitoring - Leow, Eugene Wei Chong (2015)
Shape memory materials (SMMs) plays an important role in the current society and is widely used in numerous industries that includes aerospace, automotive, telecommunication, robotics, medicine and even dentistry. It provides an edge over conventional materials with the ability to undergo controlled shape memory effect (SME), where a deformed material can restore its original shape with the appropriate stimulus. In addition to SME, SMMs possess temperature memory effect (TME) where particular temperature(s) in the previous heating process(es) can be memorised and revealed subsequently. TME has been discovered and extensively studied in certain shape memory alloys (SMAs) but has yet been solely observed in shape memory polymers (SMPs). This final year report aims to investigate on the existence and mechanism of TME in SMPs and the feasibility of integration into real life applications, such as in the replacement of conventional temperature sensors in monitoring instances of overheating and overcooling events. The material that this report will focus on is Thermoplastic Polyurethane (TPU) 265A and differential scanning calorimetric (DSC) test will present the TME results by investigating into the heat energy difference of the material. The traditional single and double stop cycles are notably expanded into multiple stop cycles in this report with studies into other external variables such as heating rates to better study the limiting conditions of TME in SMPs. With the nature and pattern fully comprehended, the effort and time required to analyse and understand future SMPs can be greatly reduced. In addition to determining the TME accuracy of TPU 265A, the data in this study can also be used in comparison with future works for evaluation of performance.